2014
DOI: 10.1073/pnas.1422165112
|View full text |Cite
|
Sign up to set email alerts
|

An in-tumor genetic screen reveals that the BET bromodomain protein, BRD4, is a potential therapeutic target in ovarian carcinoma

Abstract: High-grade serous ovarian carcinoma (HGSOC) is the most common and aggressive form of epithelial ovarian cancer, for which few targeted therapies exist. To search for new therapeutic target proteins, we performed an in vivo shRNA screen using an established human HGSOC cell line growing either subcutaneously or intraperitoneally in immunocompromised mice. We identified genes previously implicated in ovarian cancer such as AURKA1, ERBB3, CDK2, and mTOR, as well as several novel candidates including BRD4, VRK1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
127
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(135 citation statements)
references
References 36 publications
8
127
0
Order By: Relevance
“…These findings are also consistent with previous reports in multiple myeloma (6,44), acute lymphoblastic lymphoma (7), and medulloblastoma (38) cell lines where a correlation between MYC repression and growth inhibition was observed.…”
Section: Discussionsupporting
confidence: 93%
“…These findings are also consistent with previous reports in multiple myeloma (6,44), acute lymphoblastic lymphoma (7), and medulloblastoma (38) cell lines where a correlation between MYC repression and growth inhibition was observed.…”
Section: Discussionsupporting
confidence: 93%
“…Other mutated genes that play a part in the pathogenesis of HGSC and that could also serve as potential therapeutic targets for ovarian cancer include AURKA, ERBB3, CDK2, MTOR, BRD4, and MYC (63,77,78). For example, one study showed that activity of the epigenetic transcription modulator, bromodomain-containing protein 4 (encoded by BRD4) is required for the proliferation and survival of HGSC cell lines (77).…”
Section: [H2] Molecular Alterationsmentioning
confidence: 99%
“…For example, one study showed that activity of the epigenetic transcription modulator, bromodomain-containing protein 4 (encoded by BRD4) is required for the proliferation and survival of HGSC cell lines (77). Also, ovarian cancer cells sensitive to BRD4 inhibition have high expression of MYC, another important gene found altered in HGSC (77).…”
Section: [H2] Molecular Alterationsmentioning
confidence: 99%
“…In addition, high-level recruitment of BRD4 to enhancer regions has been implicated in gene-specific transcriptional activation. Evidence from a variety of approaches has implicated BET proteins, in particular BRD2 and BRD4, in a range of cancers (1,(3)(4)(5) and inhibition of BET proteins offers a novel strategy for the treatment of cancer (3,6). BET inhibitors (BETi) are small molecules that interact with the acetylated lysine binding pocket of the BET family bromodomains (6,7), interfering with BET protein binding to chromatin and consequent modulation of transcription.…”
mentioning
confidence: 99%